A política econômica dos ex-presidentes FHC e Lula nas charges do jornal O Globo (1995-2010) - Berto, Ligia Carla Gabrielli (2019)
This dissertation analyzes metaphorical messages published through the cartoons of the former presidents of Brazil, Fernando Henrique Cardoso and Luiz Inácio Lula da Silva, published in the newspaper O Globo, between 1995 and 2010. The cartoons are enunciated, of a communicative situation that depends on the historical moment in which it was produced, but which are transformed with each reading. As such, they are subject to the most diverse influences, from the author's projection through his personal and professional ideologies, and the editorial submission of the vehicle of communication. Bakhtin's concepts of heteroglossy, dialogism, and intertextuality help us to interpret the layers of meaning that make up cartoons. The methodology consists of taking the examples for analysis and comparison of the examples classified by the economic policy of the two governments. The analysis verifies the strategies of constructing criticism through irony, parody, or metaphor. The plurality of themes also allows a historical narrative of the facts and the recurrence in which metaphors explore themes such as arts, cinema, nature, animals, sports and specific references such as photo reproduction. It is noticeable that the debauched narratives do not always refer to a laughable content.